Alkaline Sucrose Gradient Sedimentation of Chromosomal Deoxyribonucleic Acid from Escherichia coli PolA(+) and PolA(−) Strains During Thymine Starvation - Sedgwick, Steven G. (1971)
Single-strand breaks were not detected in the deoxyribonucleic acid of Escherichia coli after thymine starvation for up to 180 min, even in a sensitive PolA(−) strain.